Relevance, pragmatics and interpretation - Carston, Robyn; Clark, Billy; Scott, Kate 1976- (Cambridge, United Kingdom Cambridge University Press, 2022)
"Bringing together work by leading scholars in relevance theory, this volume showcases cutting-edge research within the theory, and demonstrates its influence across a range of fields including linguistics, pragmatics, philosophy of language, literary studies, developmental psychology and cognitive science. Organised into broad thematic strands that represent the latest research and debates, the volume shows the depth of analysis now possible after nearly forty years of intensive work in developing and applying the principles of relevance theory. The breadth of influence of the framework is reflected in the chapters of the volume, in some cases moving beyond the traditional realms of semantics and pragmatics to include discourse analysis, language acquisition, media and education. The volume will be essential reading for researchers in these fields, as well as for those already working within relevance theory or with other pragmatic theories"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Pragmatics; Relevance; Semantics; Semiotics